Infantile Spasms and Injuries of Prematurity: Short-Term Treatment-Based Response and Long-Term Outcomes. (September 2017) - Wallace, Adam; Allen, Victoria; Park, Kristen; Knupp, Kelly
The association of infantile spasms and periventricular leukomalacia and/or intraventricular hemorrhage is well documented. Data regarding early treatment-based and long-term outcomes are limited. A retrospective chart review identified children with infantile spasms born prematurely (<37 weeks) with diagnoses of periventricular leukomalacia and/or intraventricular hemorrhage. Thirteen children were included. Median gestational age was 30 weeks and age of onset of infantile spasms was 8 months. Nine children had intraventricular hemorrhage, 10 had periventricular leukomalacia, and 6 children had both. Twelve of 13 children had resolution of spasms. In responders, the successful medication was adrenocorticotropic hormone (ACTH) in 7, topiramate in 3, and vigabatrin in 2. Follow-up after a median of 7.1 years found that all patients had developmental delay but only 1 had refractory epilepsy. Standard therapies (ACTH and vigabatrin) appeared to be more effective than other treatments. Developmental delay is common in children with periventricular leukomalacia / intraventricular hemorrhage and infantile spasms, but refractory epilepsy might be less frequent.